Improving quality of malaria treatment services: assessing inequities in consumers' perceptions and providers' behaviour in Nigeria - Obikeze Eric; Onwujekwe Obinna; Uzochukwu Benjamin; Okoronkwo Ijeoma; Onwujekwe Ogochukwu C (BMC, 2010)
Abstract Background Information about quality of malaria treatment services of different healthcare providers is needed to know how to improve the treatment of malaria since inappropriate service provision leads to increased burden of malaria. Hence, the study determined the technical and perceived quality of malaria treatment services of different types of providers in three urban and three rural areas in southeast Nigeria. Methods Questionnaire was used to interview randomly selected healthcare providers about the technical quality of their malaria treatment services. Exit polls were used to obtain information about perceived quality from consumers. A socio-economic status (SES) index and comparison of data between urban and rural areas was used to examine socio-economic status and geographic differences in quality of services. Results The lowest technical quality of services was found from patent medicine dealers. Conversely, public and private hospitals as well as primary healthcare centres had the highest quality of services. Householders were least satisfied with quality of services of patent medicine dealers and pharmacy shops and were mostly satisfied with services rendered by public and private hospitals. The urbanites were more satisfied with the overall quality of services than the rural dwellers. Conclusion These findings provide areas for interventions to equitably improve the quality of malaria treatment services, especially for patent medicine dealers and pharmacy shops, that are two of the most common providers of malaria treatment especially with the current change of first line drugs from the relatively inexpensive drugs to the expensive artemisinin-based combination therapy, so as to decrease inappropriate drug prescribing, use, costs and resistance to artemisinin-based combination therapy.